2018
DOI: 10.1101/259739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Herpes ICP8 protein stimulates homologous recombination in human cells

Abstract: Recombineering has transformed functional genomic analysis. Genome modification by recombineering using the phage lambda Red SynExo homologous recombination proteins Beta in Escherichia coli has approached 100% efficiency. While highly efficient in E. coli, recombineering using the Red SynExo in other organisms declines in efficiency roughly correlating with phylogenetic distance from E. coli. SynExo recombinases are common to double-stranded DNA viruses infecting a variety of organisms, including humans. Huma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The HSV exo/SSAP, composed of a 5′-to-3′ exonuclease (UL12) and an SSAP (ICP8), is capable of promoting strand exchange in vitro (25,26). More recently, we have shown that HSV infection stimulates single-strand annealing (27), and ICP8 has been reported to promote recombineering in transfected cells (28). However, these assays do not directly address the importance of the exo/SSAP during viral replication.…”
mentioning
confidence: 99%
“…The HSV exo/SSAP, composed of a 5′-to-3′ exonuclease (UL12) and an SSAP (ICP8), is capable of promoting strand exchange in vitro (25,26). More recently, we have shown that HSV infection stimulates single-strand annealing (27), and ICP8 has been reported to promote recombineering in transfected cells (28). However, these assays do not directly address the importance of the exo/SSAP during viral replication.…”
mentioning
confidence: 99%